Budgetary VAT Compensation as a Tax-Budgetary Tool for Fiscal Consolidation in Public Finances - Viktor Synchak; Yuriy Yarmolenko (Облік і фінанси)
Thanks to its tools, the VAT budget reimbursement mechanism contributes to the implementation of fiscal consolidation in public finances; however, it still needs to be studied as an object of scientific research. The purpose of the article is to reveal the essence of fiscal consolidation in the VAT budget reimbursement mechanism and to substantiate its relationship, as a tax and budgetary instrument, with the fiscal consolidation of public finances, as well as to propose measures to balance the fiscal interests of value added taxpayers and the State Budget of Ukraine. The concept of public finances about the state budget as their main link was revealed. In this link, VAT is the most significant source in volume among tax revenues and participates in distribution and redistribution relations, due to which there is a reverse flow of funds in the form of budget tax reimbursement. It was substantiated that the budget VAT refund combines tax and budget instruments of fiscal consolidation due to the peculiarities of the value-added tax collection mechanism. The article proposes the author's concept of fiscal consolidation in the budget VAT refund mechanism. The authors clarified the definition of budget VAT refund in terms of confirming the legality of its implementation based on the results of tax audits, and not just one as provided for by the current norm of the Tax Code of Ukraine. Tax audits on the legality of budget VAT refunds are proposed to be carried out for taxpayers with a high degree of risk throughout the logistics chain of goods supplies. The main measures in the field of public finances to strengthen fiscal consolidation include increasing fiscal transparency, reducing fiscal risks, strengthening control over tax liabilities and tax credit, maintaining the arrears of budget VAT refund to the state debt at the level of 0.3 p. p. under martial law and its reduction to zero in the post-war period. The study results indicate that the balance of fiscal interests will prevent arrears in VAT budget reimbursement, reduce its impact on the state's debt obligations, and generally contribute to achieving the broad goal of fiscal consolidation in public finances.